Efficacy and safety of chemotherapy regimens for first-line treatment of advanced esophageal squamous cell carcinoma in Asia: a systematic review. Issue 9 (2nd September 2022) - Xu, Jianming; Bai, Yuxian; Li, Enxiao; Xu, Nong; Shi, Danfeng; Qian, Jing
ABSTRACT: Introduction: There is no consensus on the optimal palliative first-line chemotherapy regimen for East Asian patients with advanced esophageal squamous cell carcinoma (ESCC). Areas covered: We conducted a systematic review using a literature search of PubMed, Embase, and the Cochrane Library without date restrictions, and abstracts from major oncology congresses. Studies meeting the following criteria were included: East Asian patients ≥18 years old with metastatic/locally advanced unresectable ESCC; first-line chemotherapy; reporting of overall survival, progression-free survival, duration of response, overall response rate, and/or safety; randomized controlled trials, non-randomized controlled trials, and prospective or retrospective comparative studies. In total, 39 articles were identified for: platinum plus fluoropyrimidine (n = 9), platinum plus taxane (n = 16), platinum plus fluoropyrimidine plus taxane (n = 7), platinum plus fluoropyrimidine plus other (n = 3), irinotecan plus platinum (n = 2), taxane plus fluoropyrimidine (n = 1). Expert opinion: The available data supports both taxane plus platinum regimens and fluoropyrimidine plus platinum regimens in the first-line treatment of East Asian patients with ESCC. Compared with data from doublet chemotherapy studies, triplet chemotherapy appeared to improve ORR, but did not seem to prolong OS, possibly due to an increased incidence of adverse events.